Pemanfaatan Google Apps di era literasi digital pada siswa Sekolah Dasar - Bahrul Ulum; Frendy Aru Fantiro (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The purpose of this study was to describe the use of Google Apps in the era of digital literacy for primary school students. The research method uses descriptive qualitative research with data collection techniques using literature study. Digital literacy is the ability to use information technology from digital devices effectively in various contexts of daily life. One of the efforts of digital literacy is the use of information technology using Google Apps for education that has been provided by the google search engine company for all components of education in schools. By utilizing Google Apps in the learning process that can be opened through smartphones and tablets, it allows teachers to prepare and present learning materials online (and offline) that are easily accessible to students.